The Use of Puzzle Learning Media to Improve Student Learning Outcomes in Science Subjects for Class IV - Oktaviani, Anggi; Elmojahed, Ali (Tekno - Pedagogi : Jurnal Teknologi Pendidikan, 2023)
This study aims to determine the effect of using puzzle-based learning media on student learning outcomes in science subjects, especially in Class IV of 3 Simbarwaringin State Elementary School. Faced with low student involvement and traditional teaching methods, this study aims to determine whether puzzle media can improve student learning efficiency and understanding. This study was conducted in the form of classroom action research and implemented in two cycles, each of which includes the stages of planning, implementation, observation, and reflection. Data collection was carried out through observation, testing, and documentation. The results of the study showed a significant increase, namely an increase in student learning achievement from 56.26% in the first cycle to 81.25% in the second cycle. This finding indicates that puzzle media not only motivates students but also increases students' focus and cognitive engagement in science subjects. The novelty of this study lies in the effort to demonstrate the effectiveness of interactive media in elementary science education, which offers valuable insights for educators who want to develop an active learning environment. In conclusion, the puzzle-based approach has been shown to be beneficial for student performance, thus reinforcing the need for diverse media in elementary education.